Toll-like receptor dual-acting agonists are potent inducers of PBMC-produced cytokines that inhibit hepatitis B virus production in primary human hepatocytes - Janovec, Vaclav; Hodek, Jan; Clarova, Kamila; Hofman, Tomas; Dostalik, Pavel; Fronek, Jiri; Chlupac, Jaroslav; Chaperot, Laurence; Durand, Sarah; Baumert, Thomas F; Pichova, Iva; Lubyova, Barbora; et al. (Scientific reports, 2020)
Recombinant interferon-α (IFN-α) treatment functionally cures chronic hepatitis B virus (HBV) infection in some individuals and suppresses virus replication in hepatocytes infected in vitro. We studied the antiviral effect of conditioned media (CM) from peripheral blood mononuclear cells (PBMCs) stimulated with agonists of Toll-like receptors (TLRs) 2, 7, 8 and 9. We found that CM from PBMCs stimulated with dual-acting TLR7/8 (R848) and TLR2/7 (CL413) agonists were more potent drivers of inhibition of HBe and HBs antigen secretion from HBV-infected primary human hepatocytes (PHH) than CM from PBMCs stimulated with single-acting TLR7 (CL264) or TLR9 (CpG-B) agonists. Inhibition of HBV in PHH did not correlate with the quantity of PBMC-produced IFN-α, but it was a complex function of multiple secreted cytokines. More importantly, we found that the CM that efficiently inhibited HBV production in freshly isolated PHH via various cytokine repertoires and mechanisms did not reduce covalently closed circular (ccc)DNA levels. We confirmed our data with a cell culture model based on HepG2-NTCP cells and the plasmacytoid dendritic cell line GEN2.2. Collectively, our data show the importance of dual-acting TLR agonists inducing broad cytokine repertoires. The development of poly-specific TLR agonists provides novel opportunities towards functional HBV cure.
Keywords: hepatocyty; Hep G2 Cells; přirozená imunita; Cytokines; buňky Hep G2; interferon alfa; kultivační média speciální; cytokiny; Leukocytes, Mononuclear; lidé; replikace viru; Culture Media, Conditioned; DNA, Circular; Hepatocytes; chronická hepatitida B; kruhová DNA; Interferon-alpha; Drug Delivery Systems; Immunity, Innate; Toll-Like Receptors; lékové transportní systémy; Virus Replication; toll-like receptory; Hepatitis B virus; Hepatitis B, Chronic; leukocyty mononukleární; virus hepatitidy B; Humans